2018
DOI: 10.1002/1873-3468.13000
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐talk between sphingosine‐1‐phosphate and EGFR signaling pathways enhances human glioblastoma cell invasiveness

Abstract: We show that glioblastoma multiform (GBM) cells overexpressing the constitutively active form of the epidermal growth factor receptor [epidermal growth factor receptor variant III (EGFRvIII) and U87MG human GBM cell line overexpressing EGFRvIII (EGFR+) cells] possess greater invasive properties and have higher levels of extracellular sphingosine-1-phosphate (S1P) and increased sphingosine kinase-1 (SK1) activity than the empty vector-expressing cells. Notably, the inhibition of SK1 or S1P receptors decreases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 57 publications
2
22
0
Order By: Relevance
“…In a later study, our data indicated reduced levels of S1P in platelet-rich plasma of GBM patients ( c ) [56]. These observations point towards a key role of S1P signaling system in the pathophysiology of GBM and are in agreement with studies from other groups [87,88]. Data are adapted from Bien-Möller et al [75] and Marx et al [56] and are shown as box plots representing the median as horizontal bars as well as the 5th and 95th percentile.…”
Section: Figuresupporting
confidence: 89%
“…In a later study, our data indicated reduced levels of S1P in platelet-rich plasma of GBM patients ( c ) [56]. These observations point towards a key role of S1P signaling system in the pathophysiology of GBM and are in agreement with studies from other groups [87,88]. Data are adapted from Bien-Möller et al [75] and Marx et al [56] and are shown as box plots representing the median as horizontal bars as well as the 5th and 95th percentile.…”
Section: Figuresupporting
confidence: 89%
“…S8), indicating that the role of S1P in extrusion may be linked to its crosstalk with EGFR-ERK signaling. Indeed, ERK can stimulate production of S1P by activating Sphingosine Kinases 30,31 and S1P stimulates EGFR activation during development and in glioblastomas 32,33 . Taken together these data demonstrate that either ERK or p38 MAPK signaling dynamics can initiate ADAM17-EGFR paracrine signaling to promote extrusion of unfit cells from monolayers, therefore coordinating epithelial homeostasis.…”
Section: Resultsmentioning
confidence: 99%
“…It is now known that S1P metabolism is tightly regulated. In particular, new pieces of evidence indicating specific roles for SK1 and SK2 in different diseases, including cancer, cardiovascular system and central nervous system (CNS) affections, inflammation, and diabetes, have been recently published (Pyne et al, 2016; Cattaneo et al, 2018). In particular, the role of S1P/SK2 pathway in regulating the survival of the dopaminergic neurons has emerged, suggesting that dysregulation of this pathway might be relevant to the clinical development of Parkinson’s disease (PD); in addition, a role for SK1 and SK2 has also been suggested in the onset of AD (Pyne et al, 2016).…”
Section: Sphingosine 1-phosphate Metabolism and Signalingmentioning
confidence: 99%